MERCOSUR AND THE EU: THE FALSE MIRROR - Nolte, Detlef; Ribeiro, Clarissa Correa [UNESP] (CEDEC, 2021)
The relations with the European Union (EU) began almost with the Mercosur’s creation. After signing a first framework agreement in 1995, the EU and Mercosur began negotiating a comprehensive interregional partnership with a free trade agreement since 1999. Negotiations were conducted with ups and downs, suspended, and resumed over a period of more than 20 years, and up to Mercosur’s 30th anniversary there is still no free trade agreement ratified with the EU. Based on the broad literature on the relations between the EU and Mercosur (both by European and Latin American authors) and on the analysis of official documents and declarations from the EU and Mercosur, this paper proposes some explanations as to why these negotiations have progressed so slowly and faced so many obstacles.

As relações com a União Europeia começaram quase com a criação do Mercosul; depois de assinar um primeiro acordo-quadro em 1995, desde 1999 a UE e o Mercosul negociam um acordo inter-regional abrangente que se propõe a concretizar uma área de livre comércio. As negociações foram conduzidas com altos e baixos, suspensas e retomadas em um período de mais de 20 anos, e até o trigésimo aniversário do Mercosul ainda não existe um acordo de livre comércio com a UE ratificado. Neste artigo, pretendemos oferecer algumas explicações do porquê as negociações entre a UE e o Mercosul avançaram tão lentamente e encontraram tantos obstáculos. A nossa análise baseia-se na vasta literatura sobre as relações entre a UE e o Mercosul (tanto de autores europeus quanto latino-americanos), e na análise de documentos e declarações oficiais da UE e do Mercosul.
O MERCOSUL E A UE: O FALSO ESPELHO
Keywords: Mercosur; European Union; EU-Mercosur Agreement; Interregionalism; Mercosul; União Europeia; Acordo UE-Mercosul; Interregionalismo